Hydrodynamic modeling to optimize irrigation efficiency - Anderson, Jeffrey J., author; Guitjens, J. C., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2000)
The two-dimensional, hydrodynamic model HYDRUS-2D is used to simulate irrigation schedules for an alfalfa crop over the length of a growing season. The objective is to evaluate current practices in order to produce management alternatives that reduce irrigation drainage. HYDRUS-2D uses a finite element technique that numerically solves the Richards equation for water movement in variably saturated media. The model is calibrated by comparing its output to actual field data collected from an instrumented plot at the Newlands Agricultural Research Center in Fallon. Nevada. The simulation's scope is applied to a vertical cross-sectional study area, 21.95 m in depth by 18.50 m in width, representing half of the spacing between two parallel drains. The soil profile contains one drain and three piezometers below it. An accurate model of the site's layered soil profile is developed by selecting soil parameters that produce acceptable agreement between actual and modeled drain discharge values, as well as, root mean square error between piezometric pressure heads. The following ratio is used to determine what portion of the water leaving the soil profile is consumed by evapotranspiration, Det/(Det + Dd) where Det is the depth of water used by evapotranspiration and Dd is the depth of drainage water. Optimal results are achieved as the ratio approaches one. Using short, 24-hour intervals indicates how the ratio behaves on a daily basis during irrigation cycles and provides insight into ways to modify standard irrigation practices to create a more efficient management alternative.
Irrigation and drainage in the new millennium
Not digitized by CSUL Digital Services.
Presented at the 2000 USCID international conference, Challenges facing irrigation and drainage in the new millennium on June 20-24 in Fort Collins, Colorado.